Quality assessment of acute viral bronchiolitis clinical practice guidelines (2021)
Recently, in an attempt to reduce variability in clinical practice and produce better results for patients, several clinical practice guidelines (CPGs) for the appropriate diagnosis and management of bronchiolitis in infants have been developed. However, the quality of available CPGs for bronchiolitis management has not yet been systematically evaluated. The aim of this study was to assess the quality of acute viral bronchiolitis CPGs. We performed a systematic and exhaustive search of CPGs on bronchiolitis published from 2000 to 2014. Three independent appraisers assessed the quality of the CPGs using the Appraisal of Guidelines Research and Evaluation (AGREE) II instrument. A standardized score was calculated for each of the six domains, and the CPGS were rated as recommended, recommended with modifications, or not recommended. Six CPGs published between the years 2000 and 2014 were selected from a total of 111 citations. There was substantial agreement among reviewers (ICC: 0.75; 95% CI, 0.61–0.89). The domains that scored the highest were ‘scope and purpose’, with a mean value of 92.1% (range: 77.8–100%), and ‘clarity of presentation’ [83.3% (69.4–91.7%)]. Those that scored the lowest were ‘applicability’ [44.3% (8.3–77.1%)], and ‘stakeholder involvement’ [66.7% (47.2–94.4%)]. Three CPGS were evaluated as being recommended with modifications, and only two were recommended for use in clinical practice. Available bronchiolitis CPGs vary in quality, and the findings of the present study are useful for identifying aspects or domains where there is room for improvement in future CPGs.